HUBUNGAN ANTARA MOTIVASI KERJA DENGAN KEPUASAN KERJA PEGAWAI PADA BAGIAN SEKRETARIAT DINAS PEKERJAAN UMUM KABUPATEN KUTAI TIMUR - Supriadi, Supriadi (PREDIKSI, 2016)
This study aims to determine the motivation and job satisfaction as well as the correlation between work motivation and job satisfaction of employees in the Secretariat of Public Works Bureau of East Kutai. The method used in this research is quantitative descriptive approach. The results of this study indicate that the value of Spearman rank correlation coefficient (rs) = 0.572. The result of this calculation is greater than the critical value of the prices in the table Spearman rank correlation coefficient, for n = 65 at a significance level of 5%, that is equal to 0.240. This means that there is a correlation or a positive and significant relationship between the variables work motivation and job satisfaction variables. The results also showed that the t-test produces t (hit) = 5.534, the calculation results show that t is greater than t table contained in the table prices are critical student-t for n - 2 at the 0.05 level, ie t (hit) = 5,534> t (tab) = 1.998. This means that there is a significant relationship and influence between work motivation variable to variable job satisfaction. Thus it can be said that the formulation of the problem in this study have been answered and the research hypothesis can be received and verified.